PERANCANGAN VISUAL IDENTITY MUSEUM DR. SOETOMO SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Akbar, Taufik; Yurisma, Dhika Yuan; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2018)
Researchers made direct observations and found that Museum Dr. Soetomo has no logo or visual identity that can describe the characteristics of this place to the wider community. In this design, researchers will focus on the logo design process in an effort to increase brand awareness. The concept of logo that has been designed is the inspiration obtained from the analysis of data and keywords. Inspiration concept means the spirit to the fore. A spirit of inspiration for youth through the history education of Dr. Soetomo. In addition to creating logos, this design also designs brand guidelines that aim to provide an explanation of the value and essence of the brand that Museum has Dr. Soetomo along with guidelines for the use of logos and their applications for the implementation of design. Implementation of a designed brochure design, x-banner and merchandise intended as an informative medium that can help target audiences in knowing the Museum Dr. Soetomo